Evaluating convergent validity between RAISD and MSWO rankings across informants - Jeglum, Sara R.; Melanson, Isaac J.; O’Brien, Matthew J. (Behavioral interventions, 2023)
The Reinforcer Assessment for Individuals with Severe Disabilities (RAISD) and multiple‐stimulus without replacement preference assessment (MSWO) are evidence‐based tools used to determine preferences indirectly through interview and observation of choice making, respectively. Often, the RAISD is used to inform the stimulus array of the MSWO. However, reports frequently vary between informants. This can lead to discrepant identification of putative reinforcers and therefore has the potential for weaker or ineffective reinforcement‐based treatments. The purpose of this study was to compare RAISD and MSWO outcomes across informants (adolescent, caregiver, and teacher) and evaluate the convergent validity between the two measures. The results indicated that across participants, RAISD and MSWO results rarely produced convergent validity. Implications for practitioners and researchers are discussed.